Measuring the impact of influenza vaccination national strategy among the at risk Portuguese population - Machado, Ausenda (2020)
Yearly seasonal influenza vaccine is recommended to individuals with chronic conditions or aged ≥65 years (high-risk group). However, for these high-risk individuals, the vaccine coverage has been lower than targeted, vaccine effectiveness may be altered by age or presence of chronic conditions and the impact of the vaccination strategy is still unknown. With focus in the high-risk group, this thesis aimed contributing to the national influenza strategy by providing information on i) influenza vaccine coverage and associated factors; ii) vaccine effectiveness and iii) impact of influenza vaccination strategy at population level. Results indicate that the proportion of individuals with vaccine uptake for four consecutive seasons was only 27%. Age, having a chronic condition and use of health care were positively associated to vaccine uptake. Vaccine effectiveness was estimated in 52% against medically-attended influenza and 32% against influenza hospital admissions in the ones aged ≥65 years. The tested hypothesis of an effect modification of the vaccine by age or chronic conditions, was inconclusive, probably due to lack of power. The impact of influenza vaccination strategy indicate that on average, during the period 2014/15-2017/18, the strategy averted 715 primary care medically attended influenza; 1833 hospitalizations and 383 intra-hospital. The influenza vaccine strategy had consistent and positive benefit in the high-risk population. To maximize the impact, efforts should be conducted to increase the vaccine coverage and the results of this thesis could be used to design targeted strategies. The continuous monitoring of the vaccine effectiveness and population impact could contribute in this effort. RESUMO - A vacina contra a gripe é recomendada anualmente a indivíduos alto-risco de complicações, nomeadamente aqueles com doenças crónicas ou idade ≥65 anos. Contudo, a cobertura da vacina neste grupo de alto-risco é inferior à meta estabelecida, a efetividade pode ser modificada pela idade e pela doença crónica e o impacto da estratégia de vacinação é desconhecido. Com foco nos individuos de alto-risco, esta tese pretendeu contribuir para a estratégia de vacinação contra a gripe fornecendo informações sobre a i) cobertura vacinal e fatores associados, ii) efetividade da vacina e iii) impacto a nível populacional da estratégia de vacinação. Os resultados indicam que a proporção de indivíduos com toma da vacina nas 4 épocas foi de 27%. A idade, ter doença crónica e utilização de cuidados de saúde estavam positivamente associados à toma de vacina. A hipótese de modificação de efeito da vacina pela idade e comorbilidades foi inconclusiva, decorrente provavelmente da falta de potência do estudo. ). A efetividade da vacina foi estimada em 52% na redução de consultas e em 32% na redução de hospitalizações nos indivíduos com ≥65 anos. Por último, a estratégia de vacinação preveniu em média, durante o período em análise (2014/15-2017/18), 715 consultas, 1833 hospitalizações e 383 óbitos intra-hospitalares. A estratégia de vacinação contra a gripe teve benefícios positivos na população de alto-risco. Para maximizar este impacto devem ser realizados esforços para aumentar a cobertura e os resultados desta tese podem ser importantes no delineamento de intervenções direcionadas. A contínua monitorização da efetividade e do impacto da vacina na população poderiam contribuir para esse objetivo.